1999
DOI: 10.1111/j.1365-2621.1999.tb12288.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Dioxide Treatment of Seafoods to Reduce Bacterial Loads

Abstract: Various seafoods were treated with fresh chlorine dioxide (ClO 2 ) solutions (20, 40, 100, and 200 ppm total available ClO 2 ) in 3.5% brine for 5 min, and bacterial loads and sensory quality were evaluated after 0, 3, and 7 d storage on ice. The ClO 2 treated groups at each time period had lower bacterial counts than nontreated and brine-treated groups. The differences in bacterial counts were significant, especially for groups treated with 100 and 200 ppm ClO 2 . Treated ClO 2 solutions contained very low or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 11 publications
1
29
0
Order By: Relevance
“…They showed that, the inhibitory effect of 20% TSP treatment on Listeria count ($1.7 logs CFU/cm 2 log reduction) of trout fillets was more significant (p < 0.05) compared to 10% TSP or tap water treatments. Kim et al (1999) treated various seafood with fresh chlorine dioxide (ClO 2 ) solutions (20, 40, 100, and 200 ppm total available ClO 2 ) for 5 min. They showed that after 200 ppm ClO 2 treatment of salmon fillets, bacterial loads reduced by $1.07 log 10 CFU/g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that, the inhibitory effect of 20% TSP treatment on Listeria count ($1.7 logs CFU/cm 2 log reduction) of trout fillets was more significant (p < 0.05) compared to 10% TSP or tap water treatments. Kim et al (1999) treated various seafood with fresh chlorine dioxide (ClO 2 ) solutions (20, 40, 100, and 200 ppm total available ClO 2 ) for 5 min. They showed that after 200 ppm ClO 2 treatment of salmon fillets, bacterial loads reduced by $1.07 log 10 CFU/g.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several chemical solution (aqueous) treatments have been investigated such as hypochlorite (OCl À ), chlorine, chlorine dioxide (ClO 2 ), trisodium phosphate solution (TSP) and, acidified sodium chlorite (ASC) to eliminate pathogens from seafood (Bremer & Osborne, 1998;Kim, Huang, Marshall, & Wei, 1999;Lin, Huang, Cornell, Lin, & Wei, 1996;Mu, Huang, Gates, & Wu, 1997;Park, Rua, & Acker, 1991;Su & Morrissey, 2003). Lin et al (1996) determined bactericidal effect of aqueous chlorine and chlorine dioxide on the E. coli O157:H7, L. monocytogenes, and streptomycin-resistant (Str R )-L. monocytogenes, inoculated fish cubes (mangrove snapper).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the effect of chlorine on Vibrio cells on shrimp has been reported by Chaiyakosa, Charernjiratragul, Umsakul, and Vuddhakul (2007) and Sousa, Vieira, Patel, Hofer, and Mesquita (2001). Kim, Huang, Marshall, and Wei (1999) demonstrated the effectiveness of ClO 2 in reducing the bacterial load (aerobic plate count) of brown shrimp stored at 4°and À20°C for 3 and 7 days. In another investigation ClO 2 was reported to reduce the aerobic and psychrotrophic bacterial counts on shrimp stored at 5°C for 21 days (Andrews, Key, Martin, Grodner, & Park, 2002).…”
Section: The Use Of Chlorinementioning
confidence: 95%
“…They can be contaminated with pathogenic and spoilage bacteria during harvest, production and distribution owing to improper handling and storage. 2 The development of an easy technique for determining the temperature to which a food product has been processed (end-point temperature, EPT) is necessary not only for quality control but also for regulatory control. Although minimum processing requirements can help reduce the incidence of food-borne disease, there is still the problem of con®rming whether adequate cooking temperatures and times are used after a product has been processed.…”
Section: Introductionmentioning
confidence: 99%